Personalized Pharmacological Management of Type 2 Diabetes Mellitus: A Clinical Approach to Optimizing Therapy - Shoymardonovich, Namozov Begali; Mirzayevich, Mamarasulov Tulkinjon (American Journal of Biomedicine and Pharmacy, 2025)
The global burden of type 2 diabetes mellitus (T2DM) continues to rise, necessitating individualized treatment strategies that target specific patient characteristics and comorbidities. Personalized pharmacological management aims to optimize glycemic control while minimizing adverse effects and improving patient quality of life. This article explores the current clinical approaches to the individualized treatment of T2DM, emphasizing the integration of patient-centered variables such as age, body mass index, cardiovascular status, renal function, and risk of hypoglycemia in therapeutic decisions. Advances in pharmacogenetics, the advent of novel antidiabetic drug classes, and the expansion of evidence-based guidelines have significantly enhanced treatment precision. The review provides a comprehensive analysis of the therapeutic potential of metformin, SGLT2 inhibitors, GLP-1 receptor agonists, DPP-4 inhibitors, and insulin regimens within a personalized medicine framework. The complexity of type 2 diabetes mellitus (T2DM) necessitates a shift from conventional uniform treatment regimens toward a more nuanced, patient-specific therapeutic model. This article presents a comprehensive evaluation of pharmacological strategies customized to individual clinical profiles for optimal glycemic control and risk reduction. It explores current evidence supporting the use of various antihyperglycemic agents, including metformin, sodium-glucose co-transporter 2 (SGLT2) inhibitors, glucagon-like peptide-1 receptor agonists (GLP-1 RAs), dipeptidyl peptidase-4 (DPP-4) inhibitors, and insulin, depending on patient comorbidities, physiological parameters, and therapeutic goals. By integrating pharmacogenomics, clinical phenotypes, and evolving guideline recommendations, the article outlines a framework for maximizing treatment benefits while minimizing adverse events, thereby enhancing clinical outcomes in T2DM management.